Correlation between High Body Mass Index and Premenstrual Syndrome in Iranian University Students - Mohammadi, A. (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Despite numerous shared underlying factors between high body mass index (BMI) and premenstrual syndrome (PMS), there are very little studies on cooccurrence of these disorders. Thus, the aim of this study was to evaluate the prevalence of PMS in overweight women compared with normal weight controls. Materials and Methods: This study was a cross-sectional study. Participants were 291 university student women. The survey tool was a questionnaire containing 14 questions regarding PMS screening and another questionnaire included questions concerning demographic data. Weight and height of participants were measured in kilograms and meters. We considered BMI of more than 25 as obese. The PMS screening questions were designed based on diagnostic and statistical manual IV-TR criteria. Collected data were analyzed using the frequency tables and percentiles for describes and Chi-square test for inferences. Results: From 291 women who participated in this study, 80 cases had BMI more than 25 and 211 cases had BMI <25. In addition, 196 cases had PMS symptoms in the luteal phase of menstruation. PMS symptoms in overweight women were more than in those with BMI below 25 (83.7% vs. 61.1%). These differences were statistically significant (P < 0.001). Conclusion: High BMI may be a risk factor for occurrence of PMS.